Alcune considerazioni critiche intorno al “sovranismo” - Forges Davanzati, Guglielmo (——— Materialismo Storico ——— Rivista di filosofia, storia e scienze umane, 2019)
This paper aims at discussing the macroeconomic effects of the option of leaving the euro on the part of Italy. This option is connected with the so-called sovereignism. It will be argued that the devaluation of the new Italian currency would (i) reduce real wages, worsening income distribution; (ii) would reduce the rate of growth of labour productivity and hence economic growth; (iii) would generate financial turmoils. On the political ground, sovereignism is in line with an right wing view, although it is supported by many Italian economists who define themselves leftist. Sovereignism; Euro; Productivity; Economic Growth.